EFFECT OF WEED MANAGEMENT PRACTICES ON GROWTH AND YIELD OF PIGEONPEA [ YIELD OF PIGEONPEA [CAJANUS CAJAN (L.) MILLSP.] - VINUTHA, B. S.; PATIL, M. B. PATIL (The Bioscan, 2016)
A field experiment was conducted during kharif, 2014 at Agriculture Research Station, Almel to evalvate the optimum dosage and efficacy of new molecules of herbicides used alone or in combination with cultural methods for better management of weeds in pigeon pea. Ten treatments were replicated thrice in Randomized Complete Block Design (RCBD). Significantly higher seed and stalk yield of pigeon pea was recorded in the treatment which received application of pendimethalin 38.7% C.S @ 1.0 kg a.i. ha-1 (PE) fb imazethapyr + imaza mox 70% WG (POE) @ 70 g a.i. ha-1 and one inter cultivation at 60 DAS (19.31 and 44.42 q ha-1, respectively). Growth parameters viz., plant height (143. 93 cm), number of primary branches (14.50), total dry matter (136.74 g plant-1) and yield parameters like number of pods per plant (128.43 plant-1) and 100 seed weight (12.60 g) of pigeonpea were also increased significantly with application of pendimethalin 38.7% C.S @ 1.0 kg a.i. ha-1 (PE) fb imazethapyr + imazamox 70% WG (POE) @ 70 g a.i. ha-1 and one intercultivation at 60 DAS as compared to weedy check. Combination of pre and post emergence herbicides along with manual/mechanical method of weed control has resulted in significant increase in growth and yield of pigeonpea.